The archives of the Lords of Villafranca, Marquises of Las Navas and Counts of Risco in the lands of Ávila - Sánchez González, Antonio (Revista General de Información y Documentación, 2024)
A branch of the Dávila House, a family of conquistadors and settlers of the city of Ávila, gathered a long estate from the middle of the 13th Century onwards in this area of Castille, around Villafranca de Corneja (or de La Sierra) and nearby zones. The estate was later enlarged with the additions of the Condado del Risco (1475) and the Marquisate of Las Navas (1533). Reflecting the rise in society of the Dávila House, whose origins were related to the post of regidores of the city (city authorities) and majors of the city's fortress, the family archives --which are not known in their entirity yet-- were parceled out and moved into three different places: Villafranca, Ávila and Las Navas del Marqués. However, the greater part of these archives already resided in Las Navas del Marqués by the 17th century. Later, the Lords Villafranca-Las Navas linked with the dukes of Santisteban and of Medinaceli Ducal Archives. It was here where the archives were recognized and catalogued as they remain nowadays. In this paper, we will proceed to detail their current organization and the criteria used for their classification in full.
Keywords: Davila house; Lords of Villafranca; Counts of Risco; marquises of Las Navas; Ávila; Medinaceli ducal Archive